Losing culture : nostalgia, heritage, and our accelerated times - Berliner, David (Rutgers University Press, 2020)
"Many people talk about how we're "losing everything"--Our culture, our traditions, our roots. As calls for cultural preservation multiply across the globe, anthropology teaches us that there are different ways of thinking about loss, memory, transmissions, and heritage. In this short book, translated from the French for the first time, David Berliner contemplates what the role of the anthropologist should be in a world obsessed with maintaining the past, while also rocketing toward the future"--